Queer neorealism: Luchino Visconti's Ossessione and the Cinema conspiracy against fascism. (11th March 2019) - Fabbri, Lorenzo
Abstract: 'Cinema is the most powerful weapon' – Benito Mussolini's motto loomed in capital letters over the 1937 inauguration of the massive production hub being built in the outskirts of Rome, reminding the film industry what was expected of it. Notwithstanding the effort to deploy cinema as a key technology for governing the nation and the empire, in the early 1940s film became a battlefield for the Regime. This essay excavates from the closet of memory the story of the Cinema cell, the group of young film enthusiasts who, in fascist Italy, engaged in what today we would call 'media activism': they put their lives on the line, infiltrated the film industry, and shouldered the movie camera as their initial weapon of combat against a defiant regime. I focus on how the underground formation elaborated an iteration of filmic realism that countered the implantation in the body politic of racialized fantasies of national identity. In tracing the cell's efforts to develop a gaze on the nation that would oppose the race-driven realism advocated by Mussolini's son Vittorio, among others, I establish a genealogy for Visconti's 1943 Ossessione and its display of queerness as the authentic alternative to fascist life. By way of conclusion, I disentangle the system of intimacy and affectivity harnessed by this film from the one that postwar neorealism contributed to securing.